Justification for Use of a Single Trichrome Stain as the Sole Means for Routine Detection of Intestinal Parasites in Concentrated Stool Specimens - Kellogg, James A. (American Society for Microbiology, 1999)
Of 12,321 stool samples analyzed over a 6-year interval, 870 (7.1%) were positive for a total of 1,019 parasites, of which 1,011 (99.2%) were found in trichrome-stained smears of unconcentrated specimens while only 479 (47.0%) were detected in iodine-stained smears of concentrated samples. Stool specimens were next analyzed by trichrome staining of both unconcentrated and concentrated specimens preserved in either mercury-polyvinyl alcohol (PVA) or cupric PVA. Of 2,198 specimens, 171 (7.8%) were positive for a total of 208 parasites, 192 (92.3%) and 204 (98.1%) of which were found in the unconcentrated and concentrated specimens, respectively (P < 0.05). In our patient population, examination of a single trichrome-stained smear of a concentrated stool specimen is a cost-effective alternative to routinely analyzing both concentrated and unconcentrated specimens for parasites.